The Implementation of PLEASE Strategy to Enhance the Students Writing Skills - Rahayu, Siti (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
This classroom action research study explores the implementation of the PLEASE strategy to enhance the writing skills of eighth-grade students at SMPN 19 Kabupaten Sorong. The sample comprises 23 students, with an initial mean score of 59.61 on the pretest or diagnostic test. The study is conducted over two cycles, with the average score for posttest 1 in the first cycle showing a notable increase to 68.37. Subsequently, in the second cycle, the average score further improved to 81.79. The results demonstrate a significant enhancement in students' writing skills following the integration of the PLEASE strategy into the instructional approach. The findings suggest that the systematic focus on planning, listing ideas, evaluating content, organizing arguments logically, structuring drafts effectively, and critically evaluating work has positively impacted students' writing proficiency. The study underscores the effectiveness of the PLEASE strategy in fostering students' writing competencies and highlights its potential to support students in developing essential skills for effective written communication. The outcomes of this research contribute valuable insights into the benefits of incorporating structured writing strategies like PLEASE into classroom practices to enhance students' writing skills and promote academic success.